2018
DOI: 10.1021/acs.jpclett.8b01285
|View full text |Cite
|
Sign up to set email alerts
|

Large π-Conjugated Porous Frameworks as Cathodes for Sodium-Ion Batteries

Abstract: Organic sodium-ion batteries (OSIBs) are promising alternatives of inorganic lithium-ion batteries. The cathodes of OSIBs still suffer from low capacity, poor rate performance, and low cyclability. For the first time, we demonstrate the large π-conjugated porous frameworks (CPFs) as cathodes for OSIBs, motivated by the speculation that the CPFs are capable of enhancing charge transport, facilitating ionic diffusion, inhibiting dissolution, as well as improving stability. The batteries based on the obtained CPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 50 publications
0
64
0
Order By: Relevance
“…The sulfur atom and OH in the Reproduced with permission [145] Copyright 2013, Wiley-VCH. [58,147] The characteristics of polybenzoquinone with a sulfur atom or a hydroxyl group in the molecular structure are subsequently summarized. The main driving force for the formation of the VG 8/G hybrid architecture is the π-π interactions between Vat Green 8 and the graphene sheets.…”
Section: Polybenzoquinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfur atom and OH in the Reproduced with permission [145] Copyright 2013, Wiley-VCH. [58,147] The characteristics of polybenzoquinone with a sulfur atom or a hydroxyl group in the molecular structure are subsequently summarized. The main driving force for the formation of the VG 8/G hybrid architecture is the π-π interactions between Vat Green 8 and the graphene sheets.…”
Section: Polybenzoquinonesmentioning
confidence: 99%
“…The carbonyl activity can be predicted and judged by nucleophilic addition activity. However, some materials not only have electrochemical battery behavior based on nucleophilic addition reactions, they also show the phenomenon of pseudocapacitance behavior, which can contribute some capacity . The electrochemical reaction mechanism of ACCs in secondary batteries has only recently been explained by nucleophilic addition.…”
Section: Introductionmentioning
confidence: 99%
“…These unique structural properties are not available in other porous materials, which are typically not π-conjugated, or conventional conjugated polymers, which are nonporous. [35][36][37][38][39] Enhancement in the following electrochemical properties over common RAPs are anticipated: i) fast charge transport in the preorganized pathways including both eclipsed stacked π columns and π-conjugated intralayer skeletons, ii) the porous structure of the RCMPs serving as electrolyte reservoir iii) open channels at the nanoscale providing facile, rapid, and short diffusion paths for ion mobility, and iv) the shape-persistent polymeric nature of RCMPs guaranteeing high (electro)chemical stabilities and inhibiting the potential dissolution of the electrode materials. [34] Due to their appealing properties, the application of redoxactive COFs and redox-active conjugated microporous polymers (RCMPs), which are synthesized by incorporation of redox-active building blocks, in electrochemical energy storage is becoming a fast growing field, although still in its infancy compared to conventional linear RAPs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Wang's group designed three different types of exfoliated COFs for lithium batteries, exhibiting specific capacities of 145, 210, and 110 mAh g −1 for anthraquinone-based, benzoquinone-based, and nitroxyl radical-based COFs, respectively 19 . Recent work revealed that the pentacenetetrone-based π-conjugated COFs with active C=O bonds and inactive linkage groups in the skeletons displayed a discharge capacity of~120 mAh g −1 at a high rate of 5.0 A g −1 and a capacity retention of 86% after 1000 cycles at 1.0 A g −1 in sodium batteries 20 . The reported COFs-based cathodes for rechargeable batteries are still plauged by low capacity (~200 mAh g −1 ) and inferior rate capability, limiting their further applications 21,22 .…”
mentioning
confidence: 99%